Clinical characteristics, treatment, and prognosis of 74 2019 novel coronavirus disease patients in Hefei: A single-center retrospective study. Issue 21 (28th May 2021) - Yang, Jiazhao; Wu, Kerong; Ding, Ao; Li, Li; Lu, Hui; Zhu, Wanbo; Xie, Kai; Yao, Ziqin; Fang, Shiyuan
Abstract : Abstract: Since December 2019, pneumonia caused by a novel coronavirus (SARS-CoV-2), namely 2019 novel coronavirus disease (COVID-19), has rapidly spread from Wuhan city to other cities across China. The present study was designed to describe the epidemiology, clinical characteristics, treatment, and prognosis of 74 hospitalized patients with COVID-19. Clinical data of 74 COVID-19 patients were collected to analyze the epidemiological, demographic, laboratory, radiological, and treatment data. Thirty-two patients were followed up and tested for the presence of the viral nucleic acid and by pulmonary computed tomography (CT) scan at 7 and 14 days after they were discharged. Among all COVID-19 patients, the median incubation period for patients and the median period from symptom onset to admission was all 6 days; the median length of hospitalization was 13 days. Fever symptoms were presented in 83.78% of the patients, and the second most common symptom was cough (74.32%), followed by fatigue and expectoration (27.03%). Inflammatory indicators, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) of the intensive care unit (ICU) patients were significantly higher than that of the non-ICU patients ( P  < .05). However, 50.00% of the ICU patients had their the ratio of T helper cells to cytotoxic T cells (CD4/CD8) ratio lower than 1.1, whose proportion is much higher than that in non-ICU patients ( P  < .01). Compared with patients in Wuhan, COVID-19 patients in Anhui Province seemed to have milder symptoms of infection, suggesting that there may be some regional differences in the transmission of SARS-CoV-2 between different cities.